TiC0.5N0.5-Based Cermets with Varied Amounts of Si3N4 Nanopowders Prepared by Spark Plasma Sintering - Changchun Lv; Zhijian Peng; Zhiqiang Fu; Chengbiao Wang (Advances in Materials Science and Engineering)
TiCN-based cermets with varied fractions of Si3N4 nanopowder (0–5 wt.%) were prepared by spark plasma sintering. The microstructural and mechanical properties of these cermets were investigated. In general, with increasing addition amount of Si3N4 nanopowder the relative density as well as mechanical properties of the as-prepared TiCN cermets increased first and then decreased. The samples containing 2 wt.% Si3N4 nanopowder presented the best performance with the relative density of about 98%, bending strength of 1000 MPa, and Vickers microhardness of about 1810 HV10.